2020
DOI: 10.4269/ajtmh.20-0036
|View full text |Cite
|
Sign up to set email alerts
|

Is Malaria an Important Cause of Death among Adults?

Abstract: . A long-held assumption has been that nearly all malaria deaths in high-transmission areas are of children younger than 5 years and pregnant women. Most global malaria mortality estimates incorporate this assumption in their calculations. In 2010, the Indian Million Death Study, which assigns cause of death by verbal autopsy (VA), challenged the reigning perception, producing a U-shaped mortality age curve, with rates rising after age 45 years in areas of India with substantial malaria transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…These findings are consistent with analyses from the past decade, but which are still controversial, that challenge the long-held view that few malaria deaths occur after childhood in highly endemic areas. 16 , 24 The high malaria death toll among adults accounted for most of the large discrepancy between SL-SRS and WHO estimates. Moreover, WHO estimates do not suggest missing deaths from other acute infections, which has been suggested by commentators in response to previous reports of high levels of adult malaria mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with analyses from the past decade, but which are still controversial, that challenge the long-held view that few malaria deaths occur after childhood in highly endemic areas. 16 , 24 The high malaria death toll among adults accounted for most of the large discrepancy between SL-SRS and WHO estimates. Moreover, WHO estimates do not suggest missing deaths from other acute infections, which has been suggested by commentators in response to previous reports of high levels of adult malaria mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There are both pros and cons of VA methods [ 24 ]. Misclassification of acute febrile deaths by VA among medically unattended adults is not unexpected, and likely results in malaria being over- diagnosed in some cases and under-diagnosed in others [ 1 , 2 ]. Since this study relied only on mortality data, and comparable incidence data were not available, therefore case fatality ratios across space and time could not be compared.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria contributes not only to the global infectious disease burden, but has serious economic consequences borne largely by those in their financially productive ages. Verbal autopsy studies in India report a national estimate of 130,000 malaria deaths before 70 years of age in 2015 [ 1 ], down from about 200,000 deaths at these ages in 2005 [ 2 ]. Malaria, like most other vector-borne diseases, is characterized by spatial and temporal variations due to climatic, ecological, and human factors.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this present article is therefore to identify some of the obstacles that impede malaria vaccination usage and acceptability in African Nations in combating malaria in the region as it continues to pose a significant global public health problem. In writing this article, we searched relevant articles on malaria and vaccine usage from scientific journals and databases 1–18 …”
Section: Justification and Aim Of This Articlementioning
confidence: 99%
“…2 According to a 2020 article in the American Journal of Tropical Medicine and Hygiene, it was shown that there was a largely unacknowledged malaria burden among adults starting in later middle age in some places with intense transmission. 2,3 A study in Kenya in 2015 showed a prevalence of malaria of 28.1% in the total adult population of 1190 adults. 4 Female respondents had a 50% higher risk of having malaria compared to males (odds ratio of 1.5, p value of 0.005) with an over 6-month period prevalence rates ranging from around 40%-60% in December, January and February to around 10% between March and June.…”
Section: Introductionmentioning
confidence: 99%